Efecto anticorrosivo de pinturas de poliuretano aplicadas sobre acero galvanizado sin tratamiento superficial - Redrovan Pesantez, Felipe (2019)
The objective of this research was to demonstrate the effectiveness of polyurethane paints for the protection against corrosion of galvanized steel. The methodology consisted of performing electrochemical analysis by means of polarization curves and accelerated corrosion tests (salt spray chamber) of the behavior of the duplex and galvanized protection systems in 3.5% NaCl. In addition, the SEM analysis (scanning electron microscopy) was carried out with an EDAX analysis (X-ray spectroscopy of dispersive energy) observing the morphology and the composition of the corrosion products. According to the polarization curves, there are differences in each galvanized and duplex system in the studied medium. The duplex systems have a more positive corrosion potential than the potentials of the galvanized steel samples in the salt fog chamber (-950mv, -1070mv of duplex steel and -1065mv, 1080mv of original duplex steel). The corrosion rates for the galvanized and duplex steel found were 4.8528 x 10-4 1.8045 x 10-5 cm / year respectively in the salt spray chamber. These exposure conditions make it clear that the duplex system behaves more protective than the galvanized system. From the EDAX analysis it was found that the corrosion products that would be expected to be found in the case of the oxide formed in galvanized steel after experimentation in the salt fog chamber would be a mixture of zinc and iron salts such as zincite, hydrocincite, simonkoleite, and hematite for iron, as well as soluble salts (chlorides) of these metals, as well as iron and zinc oxides, as well as zinc and iron in their metallic state.